Clinical Characteristics of Radiation Oncology in Korea during Past 10 Years - Ji, Young Hoon; Kim, Mi Sook; Jung, Haijo; Yoo, Seong Yul; Cho, Chul Koo (Journal of Korean medical science, 2009)
To understand trends in the clinical characteristics of radiation oncology over the last 10 yr in Korea, annual survey questionnaires were sent to all of Korean radiation oncology facilities since 1990. Questionnaires addressed basic radiation therapy facilities and the clinical information. Responses were obtained from all facilities, and data collected from 1997 to 2006 was analyzed. The numbers of new patients that have undergone radiation therapy and the numbers of hospitals with a department of radiation oncology have steadily increased over the past 10 yr, and totaled 37,215 patients and 60 hospitals, respectively, in 2006. However, the proportion of patients irradiated among total cancer patients has remained below 30% over the last 10 yr. The numbers of prostate cancer, breast cancer, and hepatoma have increased by more than 3 fold over the past 10 yr. Moreover, the percentage of irradiated patients treated by brachytherapy was 10.3% in 1997, but this gradually fell to only 4.2% in 2006. The information collected described the role played by radiation oncology in Korea. Continuous surveys are required to enable trends to be detected.